How mentoring education affects nurse mentors’ competence in mentoring students during clinical practice:a quasi‐experimental study’ - Tuomikoski, A.-M. (Anna-Maria); Ruotsalainen, H. (Heidi); Miettunen, J. (Jouko); Juvonen, S. (Sari); Sivonen, P. (Pirkko); Kääriäinen, M. (Maria) (John Wiley & Sons, 2020)
Abstract Background: Mentors need diverse competencies, sources of motivation and characteristics to successfully mentor nursing students and support students’ learning processes. Effective mentoring education can benefit future nursing professionals, students’ satisfaction and learning, as well as the general perception of the nursing profession. Objective: The purpose of this study was to evaluate how an educational intervention affects nurse mentors’ competence in mentoring nursing students during clinical practice. Design: A quasi‐experimental study design with pre‐ and post‐tests was used. Settings: Educational interventions were conducted in one university hospital and two central hospitals in Finland between 2013 and 2017. The intervention was conducted twice per year with a duration of 3 months for each group. The inclusion criteria for the participants were as follows: volunteer participation to mentor education employment at the university hospital or central hospitals in Northern Finland. Methods: The intervention aimed to increase Registered Nurses’ competence in mentoring nursing students. The education lasted 3 months and included online learning as well as three face‐to‐face teaching sessions. A total of 120 nurse mentors completed the Mentor Competence Instrument (MCI), which includes 10 subscales that describe various competence areas, before and after the education. Results: Nurse mentors’ mentoring competence increased across all mentoring competence areas after the educational intervention. More specifically, the participating nurses showed a statistically significant increase in their competence regarding knowledge of mentoring practices in the workplace, student‐centred evaluation, identifying student needs, mentoring practices between mentor and student, supporting students’ learning processes, goal orientation in mentoring and constructive feedback. Conclusions: On an international level, nurse mentors are not typically required to have completed mentoring education prior to the mentoring ...